An Increased Monocyte Count Predicts Coronary Artery Spasm in Patients with Resting Chest Pain and Insignificant Coronary Artery Stenosis - Yun, Kyeong Ho (The Korean Association of Internal Medicine, 2006)
BACKGROUND: Coronary atherosclerosis with inflammation gives rise to coronary vasospasm in the patients with coronary vasospastic angina. We have postulated that the peripheral leukocyte count and the differential count are associated with vasospastic angina. METHODS: 144 patients who underwent intracoronary ergonovine provocation testing between January 2002 and December 2004 were divided into two groups: Group I (72 patients with provoked spasm, mean age: 54.8±10.7 years, males: 75%) and Group II (72 without spasm, mean age: 55.3±10.2 years, males: 35%). Blood sampling was done to measure the lipid profiles and inflammatory markers, including the high sensitive C-reactive protein (hsCRP) levels and the monocyte counts. We compared the angiographic findings and laboratory data between the two groups. RESULTS: There were no significant differences in the levels of serum lipid and hsCRP between the two groups. The white blood cell count and the monocyte count were higher in Group I than with Group II (7496.4±2622.28 vs. 6703.2±1768.37/mm(3), respectively, p=0.035; 627.5±270.70 vs. 426.9±205.76/mm(3), respectively, p<0.001). Gensini's score was higher in Group I than in Group II (2.2±2.88 vs. 0.5±1.03, respectively, p<0.001). Multivariate analysis showed that the monocyte count and Gensini's score were independent factors affecting coronary spasm (p=0.047 and p=0.018, respectively). According to a receiver operating characteristics curve analysis, the area under the curve of the monocyte count was 0.738, that of the neutrophil count was 0.577 and that of the WBC count was 0.572. The cut-off value of the monocyte count was 530/mm(3); the sensitivity and specificity of this cut-off value were 64% and 76%, respectively. CONCLUSIONS: The peripheral monocyte count is an independent marker for predicting vasospastic angina in the patients with resting chest pain and insignificant coronary artery stenosis.